Evaluation of clinical teaching and professional development in a problem and community-based nursing module - J.C de Villiers; A. Joubert; C.J. Bester (AOSIS, 2004)
In South Africa the main focus is on primary health care. This affects the education and training of nurses, and training schools must respond by developing appropriate teaching modules. A school of nursing developed, implemented and revised a problem- and community- based learning module over a period of three years (1996-1998). This student-centered module focuses on students' needs, active participation, collaboration, accountability, self-assessment, self-study, life-long learning and appropriate skills. In the formal clinical teaching environment PBL was the main approach. However, this approach was also supported by a variety of strategies, for example group discussions and scenarios. The knowledge, attitudes and professional development skills acquired in the PBL approach were then applied informally in the community setting (CBE). The purpose of the study was to evaluate a first year clinical teaching module as part of an extensive programme. A quantitative research method, a descriptive design, and a variety of data collection techniques were used. Conclusions were that clinical teaching was effective within the problem- (PBL) and community-based (CBE) approaches; 78% of respondents were positive about the clinical learning environment; 61 % stated that expectations were met; 81% preferred group activities, and 67% indicated that they had developed professional skills. Facilitators agreed that clinical teaching met the requirements of PBL & CBE. The pass rate also improved.